Assessment Strategies Implemented by Novice Teachers at An English Language Course Institution - Utama, Hasna Aisyah Iman; Pratolo, Bambang Widi (IKIP Siliwangi, 2025)
The study focuses on the assessment strategies implemented by novice teachers at an English language course institution. Through descriptive qualitative research, the study investigates the types of assessment strategies used by these teachers and how they implement them in the classroom. Using open-ended questionnaires and observations, data were collected from three teachers with 1-2 years of teaching experience. The findings reveal that all three teachers predominantly used formative assessment, which includes exercises, written tests, and oral questions to gauge student understanding during the learning process. Each teacher employed different methods tailored to their students’ needs, emphasizing the importance of formative assessment in improving student learning outcomes. The study concludes that while the specific strategies vary, the common goal among the teachers is to assess students’ progress systematically to enhance learning. This research contributes to the ongoing discussion of effective assessment practices in English language teaching, highlighting the challenges and successes of novice teachers in this context.